New Species of Nyctibatrachus (Anura: Ranidae) from Castle Rock, Karnataka State, Southwest India - Das, I.; Kunte, Krushnamegh (The Society for the Study of Amphibians and Reptiles, 2005)
A new species of ranid frog of the genusNyctibatrachusis described from Castle Rock,Karnataka State, Southwest India. The new species is compared with all known congeners and is diagnosedby the following combination of characters: head wider than long; snout projecting beyond mouth;supratympanic fold poorly defined; webbing on toes reaching base of disks except on Toe IV, where it reachesdistal subarticular tubercle; tips of digits on fingers and toes flattened to form disks with distinct groovesseparating dorsum of disks from venter; and femoral gland present. The largest specimen in the type serieshas a snout-vent length of 43.2 mm.Nyctibatrachus hussainiKrishnamurthy, Reddy and Gururaja, 2001, isshown to be an invalid nomen, for lack of typification.